Diagnostic Accuracy of Cone Beam Computed Tomography in Identification of Foreign Bodies in the Head and Neck Region - Valizadeh, Solmaz; Alibakhshi, Leila; Ghazizadeh Ahsaie, Mitra; Kazemi, Soroush; Vasegh, Zahra (Journal of Dental School, 2019)
Objectives This study aimed to assess the identification of traumatic foreign bodies in the head and neck region using cone-beam computed tomography (CBCT). Methods In this study, samples (1×1×0.1 cm) were fabricated from 6 different types of materials commonly found in various head and face traumas. These materials included iron, glass, stone, wood, asphalt, and tooth. They were located in 3 different areas, including the tongue, airway, and vestibule of 3 sheep heads. Ten scans were acquired from these materials embedded in different regions. A total of 180 images were analyzed by 2 observers and rated in terms of visual clarity of the foreign body. The results were analyzed by the Kruskal-Wallis test. Results In 100% of images, stone, asphalt, and glass were observed in all 3 areas with high resolution. On the other hand, 100% of images were unclear in all evaluated areas with metal artifacts. Tooth images were found to be excellent in 100% of cases in the muscle and airway regions and 80% of cases in the vestibule region (unclear in 20% of cases). However, wood was not detected in 100% of images from the tongue and vestibule regions. It was not detected on 60% of images from the airway, while it was found on 40% of images with low resolution. Conclusion CBCT detected and located all opaque objects such as iron, glass, stone, asphalt, and tooth. However, it showed limited potential in detecting radiolucent objects such as wood